Effects of ankle-brachial index and brachial-ankle pulse wave velocity on all-cause mortality in a community-based elderly population - Zhang, Anhang; Liu, Yupeng; Ma, Shouyuan; Bao, Qiligeer; Sun, Jin; Su, Yongkang; Cai, Shuang; Cheng, Bokai; Li, Man; Zhang, Yan; Tao, Tianqi; Qiu, Jiaojiao; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Ankle-brachial index (ABI) and brachial-ankle pulse wave velocity (baPWV) are both important indicators of arterial stiffness and vascular injury. At present, most studies on the relationship between ABI and baPWV and all-cause mortality in community-based elderly are analyzing ABI or baPWV alone, and will focus on a single special population such as diabetes and stroke. The purpose of this study was to evaluate the relationship between ABI and baPWV in a Chinese community-based elderly population, and to analyze their impact on all-cause mortality in a community-based population through a follow-up of nearly ten years. Methods: Participants were residents of the Wanshou Road community in Beijing, China. A total of 2162 people in the community were included, with an average age of 71.48 years. During a mean follow-up period of 9.87 years, 1826 subjects completed follow-up. Kaplan-Meier survival analysis and different Cox regression models were used to verify the association of ABI and baPWV with all-cause mortality. The selected subjects were divided into two groups according to ABI and baPWV, and ABI was divided into two groups with 0.90 as the cut-off point (group1: 0.9